Land reforms and population growth - Lehmijoki, Ulla (2018)
One of the greatest puzzles in demographic history is why in the rich and urbanized England, fertility declined much later than in the poor and rural France. We consider the effects of a land reform on demographic growth by a family- optimization model where relative per capita wealth generates social status and welfare. We show that tenant farming is the major obstacle to escaping the Malthu- sian trap with high fertility and low productivity. A land reform provides peasants with higher returns for their investments, inducing them to increase their productiv- ity and status rather than their family size. Consequently, the population growth rate slows down, but the productivity of land increases.